2013
DOI: 10.1016/j.yjmcc.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of direct fibroblast reprogramming to cardiomyocytes using calcium activity as a functional measure of success

Abstract: Direct conversion of fibroblasts to induced cardiomyocytes (iCMs) has great potential for regenerative medicine. Recent publications have reported significant progress, but the evaluation of reprogramming has relied upon non-functional measures such as flow cytometry for cardiomyocyte markers or GFP expression driven by a cardiomyocyte-specific promoter. The issue is one of practicality: the most stringent measures - electrophysiology to detect cell excitation and the presence of spontaneously contracting myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
202
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(207 citation statements)
references
References 44 publications
5
202
0
Order By: Relevance
“…Later studies revealed that MyoD induces myogenin through cooperation with the Pbx factor, which is constitutively bound to MyoD target sites in fibroblasts prior to MyoD expression (Berkes et al 2004). There are many other examples of direct cell conversion within the same germ layer: the combination of PU.1 and C/EBPa into macrophage-like cells from fibroblasts (Feng et al 2008) and GATA4, MEF2C, TBX5, Hand2, and NKX2.5 for cardiomyocytelike cells from fibroblasts (Ieda et al 2010;Addis et al 2013). …”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
“…Later studies revealed that MyoD induces myogenin through cooperation with the Pbx factor, which is constitutively bound to MyoD target sites in fibroblasts prior to MyoD expression (Berkes et al 2004). There are many other examples of direct cell conversion within the same germ layer: the combination of PU.1 and C/EBPa into macrophage-like cells from fibroblasts (Feng et al 2008) and GATA4, MEF2C, TBX5, Hand2, and NKX2.5 for cardiomyocytelike cells from fibroblasts (Ieda et al 2010;Addis et al 2013). …”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
“…This wave-like pattern is typical of cardiomyocytes created by direct reprogramming, whereas cardiomyocytes prepared from embryonic heart show a simultaneous increase of the fluorescence intensity in the entire cytoplasm. 4 The wave-like pattern appears to represent partially reprogrammed cardiomyocytelike cells. Indeed, only 30% of the cells expressed cTnT, a marker for terminally differentiated cardiomyocytes (see Supplementary material online, Figure S4A) on the same day that the wave-like pattern was observed.…”
mentioning
confidence: 99%
“…Ca 2+ oscillations in the cells were monitored using a transgene encoding the Ca 2+ indicator protein GCaMP5, which emits stronger green fluorescence in the presence of a higher intracellular Ca 2+ concentration. 4 When GSK126 was used from Day 1 to 4, numerous cells exhibited asynchronous oscillation of the fluorescence intensity, and thus the intracellular Ca 2+ concentration, on Day 14 (see Supplementary material online, Figure S1C and Videos 1A and 2A). Some cells were spontaneously beating (Phase and Hoechst panels in Supplementary material online, Figure S1C and Videos 1B and 2B).…”
mentioning
confidence: 99%
“…Since then, other labs around the world have reported success in reprogramming mouse fibroblasts into iCMs with similar cocktails of reprogramming factors [6][7][8][9][10]. We and others have also directly converted human cardiac and dermal fibroblasts into cardiac cells [11][12][13].…”
Section: Introductionmentioning
confidence: 95%